Woody Species Diversity and Structure of Protected Woodlands Adjacent to Free Grazing Land Woodland at Dugda Woreda, Oromia, Ethiopia - Tsegu Ereso Denbel (International Journal of Forestry Research)
The study was conducted in protected woodland and free graze woodland located in Dugda Woreda, Oromia state, Ethiopia. The objective of the study was to explore the floristic composition, structure, and regeneration of woody species. In the park, the vegetation ecology has not been studied up to date, which is necessary for conservation. The systematic sampling technique was used to collect vegetation and human disturbance (presence and absence) data from August to December 2017. The vegetation data were collected from 30 plots from each woodland with a size of 900 m2 (30 m × 300 m) for tree/shrub, while subplots of size 400 m2 (20 m × 20 m) for sapling, respectively, were established in the main plots. Individual tree and shrub diameters at breast height (DBH) ≥2.5 cm and height ≥ 2 m were measured using a tape meter and clinometer, respectively. Diameter at breast height (DBH), frequency, density, basal area, and importance value index (IVI) were used for vegetation structure description, while the densities of mature trees, sapling, and seedling were used for regeneration. A total of 446 individual stems from free grazed woodland and 641 individual stems from protected woodland with a DBH of ≥2.5 cm were encountered from 30 studied sample plots that are protected and free grazed woodlands. Of these, from the total woody species, 68.42% were trees and 31.57% shrubs found in protected woodland; 76.92% were trees and 23.07% shrubs found in free grazed woodland. The total basal area of the woody plant was 3.1 ± 1 m2/ha in free grazed woodland and 4.2 ± 2 m2/ha in protected woodland, calculated for 19 woody species. Fabaceae, Balanitaceae, Capparidaceae, Verbenaceae, and Boraginaceae families were the most abundant families in both woodlands. However, there is a good initiation for the conservation of the park; still, the vegetation of the park was threatened by human-induced fire following intensive farming, gold mining, and overgrazing.